A Deep‐UV Nonlinear Optical Borosulfate with Incommensurate Modulations. (8th April 2021) - Li, Yanqiang; Zhou, Zhengyang; Zhao, Sangen; Liang, Fei; Ding, Qingran; Sun, Junliang; Lin, Zheshuai; Hong, Maochun; Luo, Junhua
Abstract: Despite borate‐sulfates composed of isolated borate and sulfate groups have been discovered for more than one century, borosulfates of B‐O‐S bonding have not been synthesized until 2012 and their properties remain rarely explored. Here, we report a new borosulfate, namely LiRb4 [B(SO4 )4 ], which shows potential as a bran‐new class of deep‐UV nonlinear optical (NLO) material. Remarkably, according to the in situ single‐crystal X‐ray diffraction, LiRb4 [B(SO4 )4 ] undergoes successive first‐order phase transitions with incommensurate structural modulations under room temperature and low temperature with (3 + 1)D superspace groups of X 2( α 0 γ )0 and P 21 ( α 0 γ )0, respectively. The first‐principle calculations and structural analyses reveal that NLO properties, phase transitions, and incommensurate modulations are closely related to the [B(SO4 )4 ] 5− super‐tetrahedral units with B‐O‐S bonding. We anticipate that the unprecedented coexistence of deep‐UV transparency, NLO responses, and incommensurate structural modulations in one borosulfate will bring new possibilities to understand the underlying concepts of physics and chemistry in aperiodic materials. Abstract : The unprecedented coexistence of deep‐UV transparency, nonlinear optical response, and incommensurate structural modulations in a new borosulfate LiRb4 [B(SO4 )4 ] brings new possibilities to understand the underlying concepts of physics and chemistry in aperiodic materials.